Assessing the kinematics of a novel collision sport simulator - Burger, N.; Lambert, M. J.; Viljoen, W.; Brown, J. C.; Readhead, C.; Hendricks, S. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The tackle is a common and dynamic phase of play in rugby union and other collision sports. It is necessary to study the tackle to characterise its various facets that include impact force, biological markers, and technical and skill-related requirements. Therefore, a novel collision sport simulator was &signed to replicate front-on tackle situations. This study describes the movement and velocity properties of the simulator relative to the force of pressure exerted by a pneumatic system. Future research using this simulator may guide the development of skill training/conditioning sessions and injury prevention programs.